Cellular Response of Pea Plants to Cadmium Toxicity: Cross Talk between Reactive Oxygen Species, Nitric Oxide, and Calcium - Rodríguez-Serrano, María (American Society of Plant Biologists, 2009)
Cadmium (Cd) toxicity has been widely studied in different plant species; however, the mechanism involved in its toxicity as well as the cell response against the metal have not been well established. In this work, using pea (Pisum sativum) plants, we studied the effect of Cd on antioxidants, reactive oxygen species (ROS), and nitric oxide (NO) metabolism of leaves using different cellular, molecular, and biochemical approaches. The growth of pea plants with 50 μm CdCl(2) affected differentially the expression of superoxide dismutase (SOD) isozymes at both transcriptional and posttranscriptional levels, giving rise to a SOD activity reduction. The copper/zinc-SOD down-regulation was apparently due to the calcium (Ca) deficiency induced by the heavy metal. In these circumstances, the overproduction of the ROS hydrogen peroxide and superoxide could be observed in vivo by confocal laser microscopy, mainly associated with vascular tissue, epidermis, and mesophyll cells, and the production of superoxide radicals was prevented by exogenous Ca. On the other hand, the NO synthase-dependent NO production was strongly depressed by Cd, and treatment with Ca prevented this effect. Under these conditions, the pathogen-related proteins PrP4A and chitinase and the heat shock protein 71.2, were up-regulated, probably to protect cells against damages induced by Cd. The regulation of these proteins could be mediated by jasmonic acid and ethylene, whose contents increased by Cd treatment. A model is proposed for the cellular response to long-term Cd exposure consisting of cross talk between Ca, ROS, and NO.